2010
DOI: 10.1007/s00216-010-4339-7
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS determination of parabens, triclosan and methyl triclosan in water by in situ derivatisation and stir-bar sorptive extraction

Abstract: Stir-bar sorptive extraction in combination with an in situ derivatisation reaction and thermal desorption-gas chromatography-mass spectrometry was successfully applied to determine parabens (methylparaben, isopropylparaben, n-propylparaben, butylparaben and benzylparaben), triclosan and methyltriclosan in water samples. This approach improves both the extraction efficiency and the sensitivity in the GC in a simple way since the derivatisation reaction occurs at the same time as the extraction procedure. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 50 publications
1
43
1
Order By: Relevance
“…Parabens have been found in surface waters at levels as high as 3,142 ng/L [66,67]. Methylparaben and propylparaben, which are the most commonly detected parabens in waters (in agreement with their extensive use in cosmetic formulations), have been quantified in tap water at levels up to 40 [68,69] and 135 ng/L [70], respectively. The main concerns regarding the presence of parabens in the environment arise from their endocrine disrupting potential and their possible involvement in the process of carcinogenesis, both of which are currently under investigation [67].…”
Section: Pharmaceuticals Antibacterials and Hormonesmentioning
confidence: 97%
“…Parabens have been found in surface waters at levels as high as 3,142 ng/L [66,67]. Methylparaben and propylparaben, which are the most commonly detected parabens in waters (in agreement with their extensive use in cosmetic formulations), have been quantified in tap water at levels up to 40 [68,69] and 135 ng/L [70], respectively. The main concerns regarding the presence of parabens in the environment arise from their endocrine disrupting potential and their possible involvement in the process of carcinogenesis, both of which are currently under investigation [67].…”
Section: Pharmaceuticals Antibacterials and Hormonesmentioning
confidence: 97%
“…Moreover, they found better results when using PDMS-DVB or DVB-CAR-PDMS fibers compared to PA fibers, but it should be taken into account that they extracted the acetylated derivatives instead of the more polar underivatized ones as in the other papers. As can be seen in Table 3, SBSE has been also extensively used in the determination of preservatives, exclusively [108,109,118,123] or together with other PCPs [45,56,68,80,96] in environmental waters. Due to the lack of commercially available sorbents, PDMS has been the most used one, but recently Gilart et al found that EGS exhibits better extraction efficiency than PDMS for triclosan and triclocarban [80].…”
Section: Preservativesmentioning
confidence: 99%
“…Thus, it is common to perform a silylation [27,60,103,104,112,122,133], generally after the extraction is accomplished, or acetylation [96,106,116,117,120,123,129,132], generally during the extraction in order to increase both the extraction efficiency and volatility.…”
Section: Preservativesmentioning
confidence: 99%
“…Acetylation with acetic anhydride is normally performed in the presence of hydrogencarbonate or pyridine [6,7]; however, according to the literature [7], the use of hydrogen phosphate leads to higher extraction efficiencies than the hydrogen carbonate. Thus, in our work, potassium hydrogenphosphate was used as a basic catalyzer.…”
Section: Derivatization Conditionsmentioning
confidence: 99%
“…Because of the wide use, parabens are continuously released into the environment [3,4]. The presence of parabens was determined in wastewater [5][6][7][8][9][10], swimming pool water [8,9,11], river water [7][8][9][10]12], and even in tap water [6].…”
Section: Introductionmentioning
confidence: 99%